A Double-Blind, Randomized, Controlled Trial of Topical Polysporin Triple Compound Versus Topical Mupirocin for the Eradication of Colonization with Methicillin-Resistant Staphylococcus aureus in a Complex Continuing Care Population - S O’Grady; Z Hirji; B Pejcic-Karapetrovic; S Fung; H Dedier; J Takata-Shewchuk; K Zhang; J Conly (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Intranasal mupirocin or Polysporin Triple (PT) ointment (polymyxin B, bacitracin, gramicidin), in combination with chlorhexidine body washes, have been used for eradicating methicillin-resistant Staphylococcus aureus (MRSA), but no comparative studies have been done.